Analysis of Stability of Traveling Wave for Kadomtsev-Petviashvili Equation. (6th March 2013) - Liu, Jun; Liu, Xi; Mu, Gui; Zhu, Chunyan; Fu, Jie
Abstract : This paper presents the boundedness and uniform boundedness of traveling wave solutions for the Kadomtsev-Petviashvili (KP) equation. They are discussed by means of a traveling wave transformation and Lyapunov function.